2023
DOI: 10.1186/s12944-023-01853-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between atherogenic index of plasma and prehypertension or hypertension among normoglycemia subjects in a Japan population: a cross-sectional study

Mingjuan Tan,
Yongliang Zhang,
Ling Jin
et al.

Abstract: Objective The atherogenic index of plasma (AIP), consisting of triglycerides and high-density lipoprotein cholesterol, is applied to estimate the cardiovascular disease risk. The evidence regarding the association between AIP and prehypertension or hypertension remains inconclusive. This study was conducted to investigate the association of AIP and prehypertension or hypertension in normoglycemic subjects in Japan. Methods In the present cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Min et al have found that individuals with abnormal glucose metabolism and higher AIP levels may have a greater risk of developing cardiovascular diseases [ 25 ]. In addition, higher levels of AIP have been found to be positively correlated with the risk of hypertension and non-alcoholic fatty liver disease, which is potentially influenced by the glucose metabolic states [ 26 28 ]. Interestingly, a cross-sectional study has demonstrated a strong association among elevated AIP levels, an increased risk of IR, and the onset of type 2 diabetes [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Min et al have found that individuals with abnormal glucose metabolism and higher AIP levels may have a greater risk of developing cardiovascular diseases [ 25 ]. In addition, higher levels of AIP have been found to be positively correlated with the risk of hypertension and non-alcoholic fatty liver disease, which is potentially influenced by the glucose metabolic states [ 26 28 ]. Interestingly, a cross-sectional study has demonstrated a strong association among elevated AIP levels, an increased risk of IR, and the onset of type 2 diabetes [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Min et al have found that individuals with abnormal glucose metabolism and higher AIP levels may have a greater risk of developing cardiovascular diseases (24). In addition, higher levels of AIP have been shown to be positively correlated with the risk of hypertension and non-alcoholic fatty liver disease, with this relationship potentially in uenced by the glucose metabolic states (25)(26)(27). Interestingly, a cross-sectional study has shown a strong association between elevated AIP levels and an increased risk of insulin resistance and the onset of type 2 diabetes (5).…”
Section: Subgroup Analysismentioning
confidence: 99%
“…In 2001, Dobiásová and Frohlich proposed the AIP as an improved indicator of blood lipids [ 7 ]. Due to its affordability and accessibility, the AIP has been utilized in the treatment of various conditions, including hypertension [ 8 ], obesity [ 9 ], and metabolic syndrome [ 10 ]. Studies have also discovered a strong association between AIP and T2DM [ 11 , 12 ], with higher AIP levels indicating an increased risk of developing T2DM.…”
Section: Introductionmentioning
confidence: 99%